2013
DOI: 10.1118/1.4808359
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment of intramodality 3D ultrasound imaging for prostate IGRT compared to fiducial markers

Abstract: The overall accuracy of US (3.0 mm) is comparable to our FM workflow (2.2 mm). Since neither US nor FM can be considered a gold standard no conclusions can be drawn on the superiority of either method. Because US imaging captures the prostate itself instead of surrogates no invasive procedure is required. It requires more effort to standardize US imaging than FM detection. Since US imaging does not involve a radiation burden, US prostate imaging offers an alternative for FM EPI positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 71 publications
7
48
0
Order By: Relevance
“…For scenarios where it is not feasible to reproduce the probe position (e.g., in cases with large day-to-day patient setup errors, anatomy changes, or relatively unconstrained organs), alternative methods might be necessary. For example, US image information could be used to adjust the couch and place the organ at the treatment isocenter, 40 as is currently implemented with the Clarity 26,41 and BAT 27,28 US-based systems. In these cases, a robot could reduce interuser variability and reproduce simulation day probe-induced deformations by using image feedback or visual servoing to control probe placement (e.g., based on landmarks in the US image acquired on the simulation day).…”
Section: Discussionmentioning
confidence: 99%
“…For scenarios where it is not feasible to reproduce the probe position (e.g., in cases with large day-to-day patient setup errors, anatomy changes, or relatively unconstrained organs), alternative methods might be necessary. For example, US image information could be used to adjust the couch and place the organ at the treatment isocenter, 40 as is currently implemented with the Clarity 26,41 and BAT 27,28 US-based systems. In these cases, a robot could reduce interuser variability and reproduce simulation day probe-induced deformations by using image feedback or visual servoing to control probe placement (e.g., based on landmarks in the US image acquired on the simulation day).…”
Section: Discussionmentioning
confidence: 99%
“…Several image guidance methods have been investigated in recent years, including tumor tracking with intraprostatic fiducial markers, cone‐beam computed tomography (CBCT), and ultrasound‐based imaging (US‐image guidance) 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 . Ultrasound‐based systems are volumetric and offer better soft‐tissue visualization compared to CBCT, without additional exposure to ionizing radiations (9) . Several studies have shown that US‐based IGRT represents a reliable system for image guidance; 3 , 7 , 8 various other technical solutions may be used for ultrasound IGRT in clinical practice, either based on intramodality or cross‐modality verification methods (3) .…”
Section: Introductionmentioning
confidence: 99%
“…For the intramodality matching, the interoperator variability was found to be 1.3 , 1.4 , and 1.8, respectively, in the left-right, anterior-posterior, and superiorinferior direction. 10 For manual intermodality matching, this variability is not expected to be smaller since the tissue boundaries in CT and US are depicted very differently. [16][17][18][19] Although some of these errors might be intercepted by the safety margins used for treatment planning, and therefore will not always propagate to actual dose delivery errors, the recommended procedure in case of patient motion is always to rescan the patient with both CT and US ref .…”
Section: Resultsmentioning
confidence: 99%